Efek Warna dalam Dunia Desain dan Periklanan - Monica Monica; Laura Christina Luzar (Humaniora, 2011)
In daily life, color gives the spontaneous effect to psychological of people who see that color. When connected to the world of design and advertising, color could become one of the main tools to communicate the message. Therefore, the colour can conduce to increase the sales value or strengthen the image of product or corporate. Color is one of the important parts which can be an attraction of a product, artwork or design. Color provides excellence in design. Each color has difference psychological effects, so that a designer can choose and accommodate the colors with the product to be advertised. Perception of color will be different between one person to the others. It is influenced by the culture of certain countries. In some regions or countries, colors have different meanings, then it becomes the order of designers to compose colors that will be used so thatappropriate to the design that will be made.